MANAJEMEN STRATEGI MASJID AL-AQOBAH 1 PT PUSRI PALEMBANG DALAM MENINGKATKAN KUALITAS JAMAAH TERHADAP WAWASAN KEISLAMAN - Karlinda Karlinda; Candra Darmawan; Amin Sihabudin (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2020)
The main problem of this research is how the Al-Aqobah 1 mosque of PT. Pusri in improving the quality of worshipers towards Islamic insights, which has the aim: 1) to find out what programs are implemented by the Al-Aqobah 1 mosque in improving the quality of Islamic worshipers. 2) to find out the planning, implementation and evaluation implemented by the Al-Aqobah 1 mosque to improve the Islamic quality of the worshipers. This type of research is descriptive qualitative with the theory of strategy management, this study uses the method of data sources and data collection. while data collection is done by observation, interview and documentation. Data sources were interviewed by the mosque management board, including secretaries, members of the field (preaching and worship services, education and youth and youth affairs, the field of community social activities, general and equipment, and majelis ta ‟lim), TPA directors, LTTQ holders, chairpersons ACMY, ustazah TPA, daily administrators and worshipers. The results of this study indicate that the strategic management of the Al-Aqobah 1 mosque in improving the quality of worshipers with Islamic insights in accordance with the theory of strategy management put forward by Thomas and David. The program created by the Al-Aqobah mosque is an activity that starts for children, adolescents, adults and the elderly. This activity is made in accordance with fields such as TPA, Qur'an House, Studies, recitation, equipment, seminars, training and others. Planning is carried out starting from equipment or facilities to teaching staff or speakers. Implementation is carried out with regard to the conditions of time and place. And finally the evaluation carried out by the management of the Al-Aqobah mosque that is every year 2 times, monthly, weekly and evaluation of each activity. Keyword : Strategy Management, Quality